Association of sago plants with weeds in agroecosystem in Ambon Island, Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Uluputty MR, Botanri S, Kamsurya M, Pelu J, Goo N, La Habi M, Umasangadji A. 2025. Association of sago plants with weeds in agroecosystem in Ambon Island, Maluku, Indonesia. Biodiversitas 26: 3105-3112. Sago plays an important role in maintaining food security in some areas in Indonesia, including in Maluku. Nonetheless, there is limited knowledge regarding weed species in the context of sago agroecology. The research aims to investigate interspecific association between sago plants and various weed species in sago cultivation ecosystem in Ambon Island, Maluku. Data collection was conducted by establishing 100 observation plots in three sampled areas where sago field occurred. Interspecific association was determined through two stages of analysis, namely determining the presence of association between species simultaneously, and continued by measuring the level of association between paired species. The results of pairwise chi-square analysis show that there is negative association within the same sago species and between three sago species of Metroxylon rumphii, M. longispinum, and M. sylvestre, indicating competition among them. Meanwhile, negative association between sago species and non-sago species occur with two species, namely Nephrolepis exaltata, and Homalomena rubra, suggesting that these two species act as weed in sago agroecology in Ambon Island. The findings of this study emphasize the attention to reducing the competition among sago plants as well as controlling the disturbance from the two weed species to increase sago yield quality and productivity.
Keywords: Ecosystem, Jaccard Index, Metroxylon, weed associations